A transformative approach for ombudsman requirements in Malaysia / Muhamad Ikhwan Mohd Zain, Nur Ezan Rahmat and Ibtisam@Ilyana Ilias - Mohd Zain, Muhamad Ikhwan; Rahmat, Nur Ezan; Ilias, Ibtisam@Ilyana (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
In 2016, the Ombudsman for Financial Services (OFS) was established in Malaysia as the official scheme operator of the ombudsman. It operates as an alternative dispute resolution (ADR) platform for consumers and financial service providers, attempting to obtain satisfactory outcomes for all parties while adhering to transparency and accountability. However, no standard measurement or explicit criterion is indicated in the legislation for the certification or qualification of an ombudsman officer. This lack of standardisation raises concerns about the competency and skill of the individuals working as ombudsman officers, thereby weakening the OFS's efficacy in resolving financial issues. This paper seeks to fill this gap by investigating several other ADR officers' current procedures and qualifications in Malaysia. This paper aims to establish prospective benchmarks and best practices for ombudsman officers in Malaysia by researching the qualifications and procedures of ADR officials in the present institution. This will help to develop a more comprehensive structure for certifying and qualifying individuals for the role, thereby improving the OFS's credibility and efficacy in resolving financial disputes. This paper employs library-based research, a statutory approach, and a comparative method to examine existing frameworks and find best practices. The primary findings from evaluating other ADR institutions can assist in identifying potential gaps or areas for improvement in the current system, enabling the establishment of a more complete and powerful ombudsman system. The practical implications of this paper are essential for policymakers and stakeholders in enhancing the certification and qualification process for individuals in the ombudsman role. Overall, having a legislative necessity for an ombudsman officer is critical for fostering justice and resolving problems in financial disputes, enhancing trust and confidence among consumers.